Association of systemic immune-inflammation index (SII) with epigenetic age acceleration in adults: insights from NHANES - Rundong Liu; Mingjie Liu; Chendong Wang; Zhen Tao; Guangyuan Hu (Epigenetics)
The Systemic Immune-Inflammation Index (SII), a marker of systemic inflammation, has been linked to various age-related diseases, but its association with Epigenetic Age Acceleration (EAA) remains underexplored. This study aimed to investigate the SII and EAA relationship. We analysed data from 1,915 participants from the National Health and Nutrition Examination Survey (NHANES). SII was calculated as platelet count × (neutrophil count/lymphocyte count). EAA was defined as HorvathAccel, HannumAccel, Skin&BloodAccel, PhenoAgeAccel, GrimAge2Accel, and DunedinPoAm. These metrics were derived utilizing the residual method. Multivariate linear regression, smooth curve fitting, threshold effect analyses, and subgroup analyses were employed to assess the relationship between the SII and EAA. Higher SII levels were significantly associated with HannumAccel, PhenoAgeAccel, GrimAge2Accel, and DunedinPoAm. Threshold effect analyses revealed non-linear relationships, with inflection points at SII values of 24.200, 12.553, 7.766, and 10.133, respectively. Subgroup analyses identified sex, age, poverty-to-income ratio, and marital status as significant effect modifiers. The elevated SII was associated with accelerated epigenetic ageing.